2007
DOI: 10.1128/jb.00718-07
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the MexAB-OprM Multidrug Pump of Pseudomonas aeruginosa : Component Interactions Defined by the Study of Pump Mutant Suppressors

Abstract: In an effort to identify key domains of the Pseudomonas aeruginosa MexAB-OprM drug efflux system involved in component interactions, extragenic suppressors of various inactivating mutations in individual pump constituents were isolated and studied. The multidrug hypersusceptibility of P. aeruginosa expressing MexB with a mutation in a region of the protein implicated in oligomerization (G220S) was suppressed by mutations in the ␣/␤ domain of MexA. MexB(G220S) showed a reduced ability to bind MexA in vivo while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…In vivo experiments showed that AcrA, MexA and HlyD can be cross-linked, resulting in the detection of dimers or trimers (Zgurskaya and Nikaido, 2000;Balakrishnan et al, 2001;Nehme and Poole, 2007;Zgurskaya et al, 2009). These results were obtained in the absence of the transporter and TolC .…”
Section: The Membrane Fusion Proteinsupporting
confidence: 52%
“…In vivo experiments showed that AcrA, MexA and HlyD can be cross-linked, resulting in the detection of dimers or trimers (Zgurskaya and Nikaido, 2000;Balakrishnan et al, 2001;Nehme and Poole, 2007;Zgurskaya et al, 2009). These results were obtained in the absence of the transporter and TolC .…”
Section: The Membrane Fusion Proteinsupporting
confidence: 52%
“…5). Mutagenesis studies support this interaction: the suppressor mutations in MexA that either restore the activity of the defective MexB or mutations in AcrA that enable the functional complex with MexB all map to the ␣-␤-barrel region of MFPs (11,17). However, in all these models, the C-domain of AcrA does not contribute to interactions with TolC and AcrB, and the assembly of the AcrABTolC complex does not require any significant changes in AcrA structure.…”
Section: Resultsmentioning
confidence: 94%
“…The replacement of aa 290 to 357 of AcrA with an analogous region of YhiU disrupted AcrA function possibly because of the loss of interaction with the AcrB transporter (5). Random mutagenesis of MexA identified C-terminal amino acid residues as important for MexA oligomerization and interaction with MexB (16,17).…”
mentioning
confidence: 99%
“…[113118] AcrA drives TolC to fit the transporter complex. [119] Chimeric analysis of AcrA function reveals the importance of its C-terminal domain in its interaction with the AcrB pump.…”
Section: Drug Efflux Pumps In Bacteria: Structures and Mechanismsmentioning
confidence: 99%
“…[120] Mutations at both N- and C-terminus of MexA compromise the MexAB-OprM efflux activity, with the N-terminus involved in oligomerization of MexA and/or interaction with OprM and the C-terminus in interaction with the transporter MexB. [115, 118, 121] Construction of the chimeric, functional AcrA-MexB-TolC complex has suggested a certain degree of flexibility in accommodation. [122] In addition, there are paired MFPs as shown with TriAB of P. aeruginosa , which are both essential for TriABC-mediated triclosan resistance.…”
Section: Drug Efflux Pumps In Bacteria: Structures and Mechanismsmentioning
confidence: 99%